Phosphorus control in peritoneal dialysis patients - (:unkn) unknown (ELSEVIER SCIENCE INC, 2008)
Hyperphosphatemia is independently associated with an increased risk of death among dialysis patients. In this study, we have assessed the status of phosphate control and its clinical and laboratory associations in a large international group of patients on chronic peritoneal dialysis (PD) treatment. This cross-sectional multicenter study was carried out in 24 centers in three different countries ( Canada, Greece, and Turkey) among 530 PD patients (235 women, 295 men) with a mean +/- s.d. age of 55716 years and mean duration of PD of 33 +/- 25 months. Serum calcium (Ca2+),ionized Ca2+, phosphate, intact parathyroid hormone (iPTH), 25-hydroxy vitamin D-3, 1,25-dihydroxy vitamin D3, total alkaline phosphatase, and bone alkaline phosphatase concentrations were investigated, along with adequacy parameters such as Kt/V, weekly creatinine clearance, and daily urine output. Mean Kt/V was 2.3 +/- 0.65, weekly creatinine clearance 78.5 +/- 76.6 l, and daily urine output 550 +/- 603 ml day(-1). Fifty-five percent of patients had a urine volume of <400 ml day(-1). Mean serum phosphorus level was 4.9 +/- 1.3 mg per 100 ml, serum Ca2+ 9.4 +/- 1.07 mg per 100 ml, iPTH 2677356 pg ml(-1), ionized Ca2+ 1.08 +/- 0.32 mg per 100 ml, calcium phosphorus (Ca x P) product 39 +/- 19 mg(2) dl(-2), 25(OH) D3 8.3 +/- 9.3 ng ml(-1), 1,25(OH)(2)D-3 9.7 +/- 6.7 pg ml(-1), total alkaline phosphatase 170 +/- 178 Ul(-1), and bone alkaline phosphatase 71 +/- 108 Ul(-1). While 14% of patients were hypophosphatemic, with a serum phosphorus level lower than 3.5 mg per 100 ml, most patients (307 patients, 58%) had a serum phosphate level between 3.5 and 5.5 mg per 100 ml. Serum phosphorus level was 5.5 mg per 100 ml or greater in 28% (149) of patients. Serum Ca2+ level was >= 9.5 mg per 100 ml in 250 patients (49%), between 8.5 and 9.5 mg per 100 ml in 214 patients (40%), and lower than 8.5 mg per 100 ml in 66 patients (12%). Ca x P product was > 55 mg(2) dl(-2) in 136 patients (26%) and lower than >55mg(2) dl(-2) in 394 patients (74%). Serum phosphorus levels were positively correlated with serum albumin (P<0.027) and iPTH (P = 0.001), and negatively correlated with age (P<0.033). Serum phosphorus was also statistically different (P=0.013) in the older age group (465 years) compared to younger patients; mean levels were 5.1 +/- 1.4 and 4.5 +/- 1.1mg per 100 ml, respectively, in the two groups. In our study, among 530 PD patients, accepted uremic-normal limits of serum phosphorus control was achieved in 58%, Ca x P in 73%, serum Ca2+ in 53%, and iPTH levels in 24% of subjects. Our results show that chronic PD, when combined with dietary measures and use of phosphate binders, is associated with satisfactory serum phosporus control in the majority of patients.
Keywords: phosphorus; phosphorus control; phosphate binders; calcium; dialysis; peritoneal dialysis; renal osteodystrophy; HEMODIALYSIS-PATIENTS; PARATHYROID-HORMONE; MINERAL METABOLISM; MORTALITY RISK; CALCIUM; HYPERPHOSPHATEMIA; ASSOCIATION; OUTCOMES; DISEASE; MALNUTRITION